1992
DOI: 10.1159/000211021
|View full text |Cite
|
Sign up to set email alerts
|

The Local Side Effects of Transdermally Absorbed Nicotine

Abstract: Percutaneous nicotine administration induces predominant sudorific and rubiform responses in the skin which may be accompanied by subtle piloerection, hyperalgesia and pruritus (although these signs are not overtly manifest). These dermal responses are complex and mechanisms have been proposed for the direct nicotine-stimulation of sweat glands, piloerection and vasoconstriction. These reactions are accompanied by secondary activation and release of vasodilator peptides which produce a predominating vasodilato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0
1

Year Published

1994
1994
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 15 publications
1
10
0
1
Order By: Relevance
“…This effect can be antagonized by atropine and not by hexamethonium bromide, an unspecific nACh-R antagonist. This observation together with results obtained in different animals led to the assumption that mostly m3 and m4 mACh-R were mainly involved in sweat generation (Longmore et al, 1985;Sato and Sato, 1987;Grant and Landis, 1991;Smith et al, 1992). Our results unequivocally demonstrate the presence of both nACh-R and mACh-R in myoepithelial and acinar cells of eccrine sweat glands.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…This effect can be antagonized by atropine and not by hexamethonium bromide, an unspecific nACh-R antagonist. This observation together with results obtained in different animals led to the assumption that mostly m3 and m4 mACh-R were mainly involved in sweat generation (Longmore et al, 1985;Sato and Sato, 1987;Grant and Landis, 1991;Smith et al, 1992). Our results unequivocally demonstrate the presence of both nACh-R and mACh-R in myoepithelial and acinar cells of eccrine sweat glands.…”
Section: Discussionsupporting
confidence: 86%
“…Since the extraneuronal cholinergic system has been implied in basic functions of the skin such as terminal differentiation and barrier formation, sweat and sebum secretion and microcirculation (Longmore et al, 1985;Smith et al, 1992;Schafer et al, 2001;Arredondo et al, 2002), we examined ACh-R gene expression in human skin on the mRNA and protein levels. Using affinity purified polyclonal antisera raised in different species, we performed colocalization studies, providing an exact map of the ACh-R composition in scalp epidermis and adnexal structures that may be translated into distinct functional reaction patterns.…”
mentioning
confidence: 99%
“…In addition to our quantitative analysis, we observed the most pronounced epidermal hyperplasia around the infundibula, which is well in line with the above mentioned chain of arguments. Even though epidermal hyperplasia or acneiform lesions have not been reported after transdermally applying nicotine patches, this may be due to the time required to induce epidermal hyperplasia or follicular plugging in vivo (Smith et al, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…Amongst other substances, alcohol and nicotine both lead to diarrhea when consumed in excessive amounts[92]. Several cohort studies showed increased risk for alcohol abuse after bariatric surgery[93], further complicated by a faster rise of blood alcohol concentration[94].…”
Section: Addictive Disordersmentioning
confidence: 99%